A study on public perception towards child abuse: A case study at Melaka Tengah / Nurulhidayu Abu Hasan and Nurul Hanis Ismail - Abu Hasan, Nurulhidayu; Ismail, Nurul Hanis (Faculty of Administrative Science and Policy Studies, 2013)
In this study, the researchers are focus on the public perceptions towards child abuse: A case study at Melaka Tengah. The purposes of the study is to examine how individual factor can contribute to the child abuse, to identify whether family situation is one of the factor that contribute to the child abuse and to determine whether social factor can lead to the child abuse. This research emphasize on the purpose of conducting by examining how several factors contribute to the child abuse problems such as individual factor, family factor and social factor. For this study, the researchers used Convenience Sampling as sampling technique. The researchers had distributed 100 questionnaires and 100 questionnaires also were returned. The respondents were the people in Melaka Tengah. The researchers used several methods like descriptive analysis, frequency analysis, test of nornality, realibility analysis, spearman correlation, and multiple regression. The researchers findings shows that higher numbers of respondents that answered the questionnaire were females. Based on the research, all the variables have significant relationship with child abuse. Based on the multiple regressions, it shows that family factor is the most factor contribute to the child abuse problems while individual factor is the lowest factor that contribute to the child abuse problems.